2008
DOI: 10.1002/jctb.2072
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and processing with supercritical fluids

Abstract: OVERVIEW: Extraction and processing with supercritical fluids (SCF) is increasingly gaining importance in the food, pharmaceutical and chemical industries. Supercritical fluid extraction (SCFE) using carbon dioxide (CO 2 ) as a solvent has emerged as a highly popular technology today over the conventional techniques for extraction of natural products for rapid, contamination-free, tailor-made extracts having superior quality and shelf-life and high potency of active ingredients.IMPACT: The importance of SCFE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 16 publications
(9 reference statements)
0
16
0
1
Order By: Relevance
“…These methods are commercially unfeasible due to the high capital investments . Carbon dioxide can be a potential solvent for cell disruption because of its low cost, nontoxicity, nonflammability, and easy availability . Lin et al reported the use of both subcritical and supercritical carbon dioxide as a potential solvent for cell disruption, which can significantly disrupt the microbial cell wall at a reasonable exposure time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods are commercially unfeasible due to the high capital investments . Carbon dioxide can be a potential solvent for cell disruption because of its low cost, nontoxicity, nonflammability, and easy availability . Lin et al reported the use of both subcritical and supercritical carbon dioxide as a potential solvent for cell disruption, which can significantly disrupt the microbial cell wall at a reasonable exposure time.…”
Section: Introductionmentioning
confidence: 99%
“…26 Carbon dioxide can be a potential solvent for cell disruption because of its low cost, nontoxicity, nonflammability, and easy availability. [27][28][29] Lin et al 30 reported the use of both subcritical and supercritical carbon dioxide as a potential solvent for cell disruption, which can significantly disrupt the microbial cell wall at a reasonable exposure time. They have suggested that upon penetrating into the cell membrane, CO 2 can extract intracellular components and transfer extracted material out of the cell during pressure release.…”
Section: Introductionmentioning
confidence: 99%
“…The work described here focused on determining the concentration and composition of carotenoids and fatty acids obtained by supercritical fluid extraction of Synechococcus sp. Methanol is very efficient in removing large quantities of compounds in extraction processes but it is dangerous to humans and, as a result, ethanol was used as the eluent [15]. Furthermore, the influence of pressure and temperature on the yield of the supercritical extraction process was analysed and the results were compared to those obtained in the ultrasound-assisted extraction with DMF.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Principles of Green Chemistry, the organic solvents used at pilot and industrial scale have to be replaced in the near future by non‐flammable, less toxic and more benign solvents in order to obtain sustainable processes . Carbon dioxide (CO 2 ) is an inert, inexpensive, easily available, odorless, tasteless, environment‐friendly, ideally suitable for thermally labile natural products and generally regarded as safe (GRAS) solvent . In addition, its solvent power and selectivity can be adapted according to the operating conditions.…”
Section: Introductionmentioning
confidence: 99%